Legal Findings on the Status of Doctors' Employment Relationships in Private Hospitals Based on Supreme Court Decisions - Rizza, Faisal; Mudiana Permata Sari (Journal of Law, Politic and Humanities, 2024)
Basically, a written cooperation agreement is important to bind one party to another. In practice, there are still those who do not use a written cooperation agreement in the implementation of cooperation such as the case of a doctor who does not have a cooperation agreement in any form so that if one party terminates cooperation without notice, then there is no basis that can be accounted for. Therefore, the Supreme Court in considering a fair decision decided to make an updated legal discovery regarding the status of employment relations that must be made in writing so that when a dispute arises it can be accounted for before the eyes of the law. It can be concluded that it is important for judges when deciding a case to take into account the laws that apply in society, and every decision must be made based on applicable law and the principle of justice.